Use​ ​of​ ​quantitative​ ​corpus​ ​methods​ ​for​ ​detection​ ​of​ ​Slavonicisms​ ​in​ ​modern​ ​Russian - Kristina Litvintseva; Olga Lyashevskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The starting point of this study is the hypothesis of the discursive proximity of the Church Slavonic language and Christian religious discourse of the modern Russian language. Analysing lexical structure by means of quantitative corpus methods, we show that the latter is closer to Church Slavonic than to the mainstream modern Russian language. This can serve as a proof of the specifi city of the register in question, an additional argument when deciding on its separate status. Our study is based on the material of the Russian National Corpus, namely the Church-Slavonic corpus, the Main Corpus and the Subcorpus of church-and-theologу texts. Using the log-likelihood criterion and PCA visualisations, we reveal the body of lexemes in Russian texts that can be considered Slavonicisms (церковнославянизмы) and show that the “distance” between the corpora can be measured diff erently if one takes into account adjectives, nouns and verbs separately.